Effect of tube length on the performance of cooling necklace with vortex tube cold flow generator - Nur Shuhada, Adnan; Wan Nur Adibah, Wan Hisamudin; Mohd Hazwan, Yusof; Muhammad Fadhli, Suhaimi (IOP Publishing, 2024)
The vortex tube, a compact and eco-friendly device, can generate both low-temperature cold flow and high-temperature hot flow from a room-temperature compressed gas supply. Despite its potential, there has been limited research on its application as a cooling device, particularly in the context of a cooling necklace. This study aims to fill this gap by examining the performance of the vortex tube under various conditions. The experiment was conducted indoors, with tube lengths ranging from 60 cm to 140 cm and inlet pressures from 0.2 MPa to 0.4 MPa. The results suggest that an inlet pressure of 0.4 MPa and a tube length of 60 cm are optimal for achieving the lowest temperature cold flow and minimizing heat transfer effects between the cold flow and the environment.